2009
DOI: 10.1016/j.neuropharm.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mecamylamine on ethanol and sucrose self-administration

Abstract: Neuronal nicotinic acetylcholine receptors (nAChRs) are believed to be critically involved in ethanol-related behaviors as well as in neurochemical responses to ethanol. However, discernment of nAChR contribution to ethanol reinforcement and consumption remains incomplete. The current studies examined the influence of the nAChR antagonist mecamylamine (MEC) on operant ethanol self-administration using a procedure that independently assessed appetitive and consumptive processes, and compared these findings to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…These results may support role of CB1 activity in the consumption of hedonically rewarding substances [50, 51]. These effects appear to be receptor-specific as mecamylamine, a nicotinic receptor antagonist, reduces ethanol drinking bout frequency but not intrabout composition [36], and raclopride, a dopamine D2 receptor antagonist, decreases total ethanol intake via a specific reduction in number of lick runs [38]. All together, these data strongly support the idea that specific pharmacological interventions can be aimed at reducing ethanol intake through a number of distinct mechanisms.…”
Section: Discussionmentioning
confidence: 61%
“…These results may support role of CB1 activity in the consumption of hedonically rewarding substances [50, 51]. These effects appear to be receptor-specific as mecamylamine, a nicotinic receptor antagonist, reduces ethanol drinking bout frequency but not intrabout composition [36], and raclopride, a dopamine D2 receptor antagonist, decreases total ethanol intake via a specific reduction in number of lick runs [38]. All together, these data strongly support the idea that specific pharmacological interventions can be aimed at reducing ethanol intake through a number of distinct mechanisms.…”
Section: Discussionmentioning
confidence: 61%
“…Our finding is supported by a recent study which found that mecamylamine decreased pavlovian incentive motivation for sugar (Ostlund et al, 2014) and operant self-administration, albeit at much higher doses (Ford et al, 2009). Further, an in vitro application of mecamylamine in the NAc, decreased ghrelin-mediated accumbal DA release (Palotai et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, a recent study found that pavlovian incentive motivation for sugar was disrupted with systemic mecamylamine administration (Ostlund et al, 2014). Also, systemic mecamylamine was also shown to reduce sucrose self-administration, albeit at much higher doses (Ford et al, 2009).…”
Section: Chapter 5: General Discussionmentioning
confidence: 99%
“…Several electrophysiological and behavioral studies have shown an interaction between pentameric neuronal nicotinic acetylcholine receptors (nAChRs) and ethanol (Narahashi et al, 1999;Larsson and Engel, 2004;Ford et al, 2009). Reports have also shown high-to-moderate densities of nACh receptors in mesolimbic dopamineinnervated areas (Clarke et al, 1984;Klink et al, 2001;Wonnacott et al, 2005;Champtiaux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%